Refractive Index Monitoring Technique Using a Smartphone Based on the Metal Nanoshell Array Sensing Method - Wen Cao; Yali Deng; Tingting Pan; Hui Hao; Ming Wang (IEEE Photonics Journal, 2019)
A novel surface plasmon resonance (SPR) sensor system using a smartphone based on the metal nanoshell array sensing method is proposed and developed. The micro-flow injection method was used to prepare two-dimensional colloidal microsphere template, the metal nanoshell array was fabricated by combining the microsphere template and the magnetron sputtering technology. A smartphone and a diffraction grating are employed as interrogation system, in which a fiber with a 45° polished tip connect the flashlight and the camera on the smartphone. The diffraction grating spreads the transmission spectrum over the camera's pixels to allow for repeatable measurements of wavelength shifts of the sensor. The reflection intensity of sensor can be measured by smartphone and the surrounding refractive index is monitored by the shift of the reflection spectrum. The experimental results show that the sensitivity of the SPR refractive index sensor based on the metal nanoshell array is about 927 nm/RIU for a refractive index (RI) range from 1.352 to 1.363, and the quality factor of that is about 18.5. The results show that this technique can provide a low-cost, portable and intelligent diagnostic platform for the measurement of the SPR refractive index sensor.